N‐Thiophosphorylthioureas RNHC(S)NHP(S)(OiPr)2 as an Excellent Platform for Studying the Synergy between Hydrogen‐Hydrogen Bonding and Other Families of Non‐Covalent Interactions. Issue 2 (19th November 2018) - Mitoraj, Mariusz P.; Sagan, Filip; Babashkina, Maria G.; Isaev, Alexey Y.; Chichigina, Yana M.; Safin, Damir A.
Abstract : A family of thiourea based derivatives, RNHC(S)NHP(S)(O i Pr)2 [R = Ph (YEZNUN ), 2‐MeC6 H4 (AQOYAH ), 2, 5‐Me2 C6 H3 (WARREO ), 2, 6‐Me2 C6 H3 (GUJGUO ), 2, 4, 6‐Me3 C6 H2 (AQOYEL ), PhNH (QORXUR ), 1‐naphthyl (MOWPEU )], has been studied to understand the synergy between dihydrogen and other (non)conventional non‐covalent interactions. It was established that all monomers are stabilized through intramolecular dihydrogen C–H··· H–C interactions. Additionally, C–H··· π interactions are noted in AQOYAH, WARREO, and MOWPEU ; N–H··· O interactions in AQOYAH, and WARREO ; C–H··· S interactions in GUJGUO, YEZNUN, and AQOYEL ; N–H··· S interactions in GUJGUO, AQOYEL, MOWPEU, and YEZNUN ; and N–H··· N interactions in QORXUR . The crystal structures of all the thioureas are further stabilized by the most pronounced intermolecular C–H··· H–C interactions followed by N–H··· S and C–H··· S with the formation of centrosymmetric R 2 2 (8) dimers. These non‐covalent interactions are augmented by the π··· π stacking in YEZNUN and MOWPEU ; C–H··· π in WARREO, GUJGUO, AQOYEL and MOWPEU ; N–H··· π in QORXUR . The synergy between intra‐ and intermolecular C–H··· H–C and other types of non‐covalent interactions lead to the extraordinary stability of these systems as indicated by the ETS‐NOCV Scheme Although the London dispersion forces cover ≈ 70–80 % of the overall C–H··· H–C stabilization, the covalent‐like charge delocalization based on depletion of electron charge from the σ(C–H) orbitals to the inter‐atomic H··· H region contributes notably up to 15 %. Abstract : We have synthesized a new family of substituted thioureas RNHC(S)NHP(S)(O i Pr)2 differing in donor‐acceptor properties of ancillary ligands (R = Ph, 2‐MeC6 H4, 2, 5‐Me2 C6 H3, 2, 6‐Me2 C6 H3, 2, 4, 6‐Me3 C6 H2, PhNH, 1‐naphthyl) to study the nature and cooperativity of inter‐ and intramolecular hydrogen‐hydrogen close contacts together with other types of nonconventional non‐covalent interactions.